Is spatial orientation affected by Ramadan fasting?. Issue 3 (13th May 2019) - Abdul Razzak, Rima; Mohamed, Mohamed Wael; Alshaiji, Abdulla Faisal; Qareeballa, Abdulrahman Ahmed; Bagust, Jeff; Docherty, Sharon
Abstract : Purpose: Ramadan intermittent fasting (RIF) has produced heterogeneous and domain-specific effects on cognitive function. This study aims to investigate the effect of RIF on verticality perception or estimation of subjective visual vertical (SVV) in young adults. The significance of SVV is that it is essential for spatial orientation, upon which many daily activities depend. Methodology: Verticality perception was assessed with a computerized rod and frame test (CRFT) in two visual conditions: without a surrounding frame and with a distracting tilted frame. The tilted frame condition measures level of visual dependence or reliance of visual cues for posture and orientation. In total, 39 young adult men were recruited at different stages of Ramadan fasting: 21 were tested at the end of the first week (Week 1) and 18 others at the end of the third week (Week 3) of Ramadan. Also, 39 participants were recruited to serve as a non-fasting control group. Factorial ANOVA analyses were conducted to identify the main effects of fasting status, time-of-day and the interaction between them on blood glucose levels, nocturnal sleep duration and vertical alignment errors. Findings: The main effect of fasting status on glucose level was significant ( p = 0.03). There was a significant time-of-day main effect on glucose levels ( p = 0.007) and sleep duration ( p = 0.004) only in fasting participants. Neither the main effects of fasting status nor time-of-day were significant for rod alignment errors in both visual conditions. The interaction of fasting status and time-of-day was not significant either. This may indicate that any negative effect of Ramadan fasting on activities that are critically dependent on verticality perception and spatial orientation, such as sports and driving, may not be due to verticality misperception. Originality: The present study was the first to investigate the effect of Ramadan fasting on spatial orientation. It demonstrated robustness of verticality perception to fasting status and the point of fasting during Ramadan. Verticality perception was also unaffected by time-of-day effects in non-fasting and fasting groups at two different points of Ramadan. This study corroborates others reporting heterogeneous effects of Ramadan fasting on cognitive function.